Citation practices in applied linguistics: a comparative study of Chinese expert and novice authors - Gong, Xue; Liu, Ruoxi; Ji, Chuanbo (Frontiers in Psychology, 2025)
Citation practices are crucial in academic discourse for both knowledge construction and interpersonal interaction. While prior research in academic English has explored citation practices among expert and novice authors, there is a notable gap in studies focusing on Chinese academic papers. Moreover, it remains uncertain whether insights from English-language corpora can be extrapolated to other linguistic contexts. This study presents a comparative analysis of citation practices among expert and novice authors within the field of Chinese Applied Linguistics. Utilizing a corpus of 715,000 Chinese words, we analyzed academic papers authored by both groups. Our findings reveal that citation practices between expert and novice authors are largely comparable. Specifically, integral citations were more prevalent than non-integral citations, with the cited authors predominantly occupying the subject position. In terms of citation form, the four types employed, in descending order of frequency, were summary, block quote, generalization, and quote. The analysis of reporting markers showed a predominance of discourse markers, followed by research markers, with cognitive markers being the least frequent. Notably, novice authors demonstrated certain deficiencies compared to their expert counterparts, including an overreliance on integral citations, a reduced use of generalization and block quote citations, and limited integration of information regarding reporting markers.